Respuesta :

yes you would have to solve this problem by substitution method

Answer:

(-1,4)

Step-by-step explanation:

-3x + y = 7......y = 3x + 7

so sub in 3x + 7 in for y back into the other equation

5x + 2y = 3

5x + 2(3x + 7) = 3 ...distribute thru the parenthesis

5x + 6x + 14 = 3....subtract 14 from both sides

5x + 6x = 3 - 14...combine like terms

11x = - 11...divide both sides by 11

x = -11/11

x = -1

now that we know x = -1, we can sub that back into either of the original equations to find y

y = 3x + 7

y = 3(-1) + 7

y = -3 + 7

y = 4

so we have (-1,4) as a solution....but lets check it first

-3x + y = 7

-3(-1) + 4 = 7

3 + 4 = 7

7 = 7 (correct)...it checks out

so ur solution is : x = -1 and y = 4 or (-1,4)

ACCESS MORE